2018
DOI: 10.1002/bies.201800009
|View full text |Cite
|
Sign up to set email alerts
|

How Does a Helicase Unwind DNA? Insights from RecBCD Helicase

Abstract: DNA helicases are a class of molecular motors that catalyze processive unwinding of double stranded DNA. In spite of much study, we know relatively little about the mechanisms by which these enzymes carry out the function for which they are named. Most current views are based on inferences from crystal structures. A prominent view is that the canonical ATPase motor exerts a force on the ssDNA resulting in "pulling" the duplex across a "pin" or "wedge" in the enzyme leading to a mechanical separation of the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 62 publications
2
26
0
Order By: Relevance
“…First, it was shown in the crystal structure of RecBCD that there is a ‘pin’ domain in RecC against which the fork is split enabling RecB and RecD to pull the opposite unwound ssDNA strands (Singleton et al, 2004). Second, it has been postulated that the ‘arm’ protrusion in RecB may play a direct role in destabilizing the duplex ahead of the translocating enzyme (analogous to the role suggested for auxiliary domain 2B of the PcrA helicase) (Dillingham and Kowalczykowski, 2008; Velankar et al, 1999) and a recent work showed that an arm deletion results in RecBCD’s inability to unwind DNA (Lohman and Fazio, 2018; Simon et al, 2016). In both cases, the synergy between the subunits is expressed in the separation between the domain responsible for destabilizing the fork, and the fast translocase pulling the structurally unwound strands.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, it was shown in the crystal structure of RecBCD that there is a ‘pin’ domain in RecC against which the fork is split enabling RecB and RecD to pull the opposite unwound ssDNA strands (Singleton et al, 2004). Second, it has been postulated that the ‘arm’ protrusion in RecB may play a direct role in destabilizing the duplex ahead of the translocating enzyme (analogous to the role suggested for auxiliary domain 2B of the PcrA helicase) (Dillingham and Kowalczykowski, 2008; Velankar et al, 1999) and a recent work showed that an arm deletion results in RecBCD’s inability to unwind DNA (Lohman and Fazio, 2018; Simon et al, 2016). In both cases, the synergy between the subunits is expressed in the separation between the domain responsible for destabilizing the fork, and the fast translocase pulling the structurally unwound strands.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, one model of RecBCD’s translocation postulates that the helicase subunits pull the nascent DNA strands against the pin to catalyze unwinding. Moreover, it was proposed that there is a separation between helicase translocation and unwinding, whereby RecBCD unwinds 4–6 bp of DNA using the pin in a distinct step, and only then the helicase subunits pull the unwound DNA (Lohman and Fazio, 2018). In addition, an ‘arm’ domain of RecB interacts with the DNA 12 bps ahead (Saikrishnan et al, 2008; Singleton et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The discovery of proteins capable of ATP-dependent enzymatic unwinding of duplex DNA was first reported in 1976 by Hoffmann-Berling and colleagues at the University of Heidelberg [1,2] and Mackay and Linn at the University of California, Berkeley [3]. As pointed out recently in a review by Lohman and Fazio [4], the term "helicase", referring to an ATP-dependent duplex DNA unwinding enzyme, was coined by Hoffmann-Berling in 1978 [5] and appeared in two subsequent publications in 1979 [6,7]. Even at this early stage, a suggestion was made that different helicase enzymes were unique in terms of properties and mechanism of action (e.g., processivity).…”
Section: Discovery Of Dna Unwinding Enzymes and Coining The Term Helimentioning
confidence: 99%
“…In Escherichia coli and other enteric bacteria, DSB repair and recombination require RecBCD, a complex three-subunit 330 kDa enzyme with both DNA helicase and DNA nuclease activities ( 1 , 2 , 3 ). Its multiple activities are involved in the initial steps of DSB repair and recombination (Figure 1A ).…”
Section: Introductionmentioning
confidence: 99%